Information retention in companies: a question of sustainability - García-Morales, Elisa (Anuario ThinkEPI, 2021)
It is not sustainable to keep all information indefinitely. Retention is an essential aspect of corporate information governance that facilitates data and document lifecycle management. Future trends in information technologies lead us to reflect on the methodologies available and the professional qualifications needed to find new ways to help define and implement the necessary retention policies in companies and organizations.